Greenhouse Gas Reduction Potential based on Waste Recovery Factor in Gading and Dukuh Setro Subdistrics, Surabaya - Talent Nia Pramestyawati; Rodu Dhuha Afrianisa; Muhammad Hafizhni Ath Thoyib (Jurnal IPTEK, 2023)
People’s growth and their activities increase waste generation. Therefore, efforts to reduce waste are needed, including community-based reduction efforts. This research is located in Gading and Dukuh Setro sub-districts in Surabaya City. The purpose of this study was to measure the potential for waste reduction and greenhouse gas reduction. Measurement of waste generation, waste composition, and waste density was based on SNI 19-3964-1994. The researcher conducted sampling in low, middle, and high-income areas, covering 83 families. Greenhouse gas emissions were estimated using the LandGEM (U.S. EPA) method based on the waste disposed at landfill, considering the existing reduction conditions and optimal material recovery. Solid waste generation in 2022 per year was 4.695,58 tons. The largest composition of waste consisted of biodegradable waste (37.13%), plastic waste (25.73%), and diapers and sanitary napkins (18.25%). The average density of loose waste was 152.42 kg/m3. The existing reduction had 1.47% waste bank reduction activity and 0.72% composting reduction activity, for a total reduction of 2.19%. The average optimal reduction was 52.7%, whereas the optimal reduction in the waste bank was 17.5%. The optimal composting reduction was 35.2%. Thus, the existing scenario in 2032 obtained reductions from total landfill gas of 725,498 Gg/year, methane of 193,788 Gg/year, carbon dioxide of 531,710 Gg/year, and NMOC of 8,330 Gg/year. Meanwhile, the optimal scenario for 2032 obtained reductions from total landfill gas of 239.067 Gg/year, methane of 63.857 Gg/year, carbon dioxide of 175.209 Gg/year, and NMOC of 0.412 Gg/year